Agro-Business Strategies and Objectives to Develop Sustainability - R Pazhanisamy (International Journal of Modern Agriculture, 2021)
Trends, controversies, philosophies, activities, and pending demands are explored in relation to the viability and opportunities of contemporary agribusiness. In the agribusiness market, the concept of sustainable management has recently gained traction which is primarily because of extensive dissatisfaction with the industrializing of agriculture productions and crop preparing, as well as increasing publicly pressuring over agro business companies for adopting environmentally friendly supervision practices. The lack of a coherent strategic structure for defining the most important enabling laws, services, and legislation has hampered efforts to include agribusiness in the creation of sustainable agricultural systems. This paper suggests a productivity replacement to advanced modernization system to identify sustainable techniques for improving agribusiness activities in this article. The critical value of export-led agribusiness for every nation offers a paradigmatic opportunity to explore the roots and regional specificities of neoliberalism in agriculture. This paper also examines the domain of sustainability from an agribusiness standpoint, defining thresholds or phases of sustainability in terms of viewpoints, actions, and performance indicators, and the aspects affecting a company's sustainability strategies, such as firm characteristics.